2006
DOI: 10.1024/0040-5930.63.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Die diagnostische und prädiktive Bedeutung von Kit (CD117)

Abstract: KIT (CD117) is a 145-KD transmembrane glycoprotein that is the product of the kit-gene. As a member of the subclass III family of receptor tyrosine kinases, KIT is closely related to the receptors for platelet derived growth factor alpha and beta (PDGF-A and B), macrophage colony stimulating factor (M-CSF), and FLT3 ligand. The ligand for KIT, stem cell factor (SCF), also known as steel factor or mast cell growth factor promotes the dimerisation and autophosphorylation of KIT receptors. The phosphorylated tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…CD117, the product of the c-kit gene, is a 145-kDa transmembrane glycoprotein belonging to the subclass III family of TKRs [1]. It is expressed in melanocytes, spermatogonia, breast epithelium, hematopoietic cells, interstitial cells of Cajal, and mast cells, where it is essential for maintaining normal hematopoiesis, gametogenesis, as well as growth and differentiation of other cells.…”
Section: Introductionmentioning
confidence: 99%
“…CD117, the product of the c-kit gene, is a 145-kDa transmembrane glycoprotein belonging to the subclass III family of TKRs [1]. It is expressed in melanocytes, spermatogonia, breast epithelium, hematopoietic cells, interstitial cells of Cajal, and mast cells, where it is essential for maintaining normal hematopoiesis, gametogenesis, as well as growth and differentiation of other cells.…”
Section: Introductionmentioning
confidence: 99%
“…The fusion oncogene BCR–ABL in CML encodes the constitutively active BCR‐ABL tyrosine kinase, which leads to the substrate protein being activated by the phosphorylation of one of the tyrosine residues and subsequent activation of downstream effector molecules 33–35 . Inhibitors of kinase activity of ABL, c‐kit (CD117) and PDGFR such as imatinib, are thought to act by occupying the kinase ATP‐binding site, so that the kinase action is inhibited, preventing substrate phosphorylation, which prevents cell proliferation and tumorigenesis 21,23,31–33,36 . It has recently been reported that the PDGFR pathway is a major component in DFSP tumorigenesis 18,20 and imatinib has been shown to inhibit the growth of DFSP cells both in culture and in nude mice, with preliminary results from clinical trials appearing promising 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Inhibitors of kinase activity of ABL, c-kit (CD117) and PDGFR such as imatinib, are thought to act by occupying the kinase ATP-binding site, so that the kinase action is inhibited, preventing substrate phosphorylation, which prevents cell proliferation and tumorigenesis. 21,23,[31][32][33]36 It has recently been reported that the PDGFR pathway is a major component in DFSP tumorigenesis 18,20 and imatinib has been shown to inhibit the growth of DFSP cells both in culture and in nude mice, with preliminary results from clinical trials appearing promising. 37,38 Optimal treatment protocols…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the ligand for the c-kit receptor not only is stem-cell factor, but also steel factor. Mutations of KIT cause constitutive activation of the tyrosine kinase function of KIT [17]. Mutations can be subdivided into primary and secondary mutations.…”
Section: The Kit and Pdgfra Mutationsmentioning
confidence: 99%